Langerhans cells protect from allergic contact dermatitis in mice by tolerizing CD8+ T cells and activating Foxp3+ regulatory T cells - Mercedes Gomez de Agüero; Marc Vocanson; Fériel Hacini-Rachinel; Morgan Taillardet; Tim Sparwasser; Adrien Kissenpfennig; Bernard Malissen; Dominique Kaiserlian; Bertrand Dubois (The Journal of Clinical Investigation, 2012)
Allergic contact dermatitis is the most frequent occupational disease in industrialized countries. It is caused by CD8+ T cell–mediated contact hypersensitivity (CHS) reactions triggered at the site of contact by a variety of chemicals, also known as weak haptens, present in fragrances, dyes, metals, preservatives, and drugs. Despite the myriad of potentially allergenic substances that can penetrate the skin, sensitization is relatively rare and immune tolerance to the substance is often induced by as yet poorly understood mechanisms. Here we show, using the innocuous chemical 2,4-dinitrothiocyanobenzene (DNTB), that cutaneous immune tolerance in mice critically depends on epidermal Langerhans cells (LCs), which capture DNTB and migrate to lymph nodes for direct presentation to CD8+ T cells. Depletion and adoptive transfer experiments revealed that LCs conferred protection from development of CHS by a mechanism involving both anergy and deletion of allergen-specific CD8+ T cells and activation of a population of T cells identified as ICOS+CD4+Foxp3+ Tregs. Our findings highlight the critical role of LCs in tolerance induction in mice to the prototype innocuous hapten DNTB and suggest that strategies targeting LCs might be valuable for prevention of cutaneous allergy.